Framing and Navigating Breastfeeding as a Development Issue - Sentiela Ocktaviani; Angga Sisca Rahadian (LIPI Press, 2019)
This study addresses the issue of working mothers who give exclusive breastfeeding to their babies. During this time, public overlooks breastfeeding activities by considering breastfeeding merely as a mother's duty and a mundane matter. The involvement of her husband, family, community, and government to support the success of exclusive breastfeeding is still lacking. Workers' mothers have a dual role, domestic and public duties. Breastfeeding is often a barrier to women's performance in the public sphere and indirectly it impacts on household financial conditions. On the other hand, exclusive breastfeeding provides many benefits, primary for health and economic benefits. Therefore, this study wants to analyze breastfeeding activities through the development paradigm and finds the proper strategy for stakeholders to navigate breastfeeding as a development activity. The approach used in this research is qualitative by conducting interviews with stakeholders and literature review. The concepts of gender and development are applied to analyze the involvement of partners, families and communities in supporting the achievement of exclusive breastfeeding. The government also has an essential role in ensuring women and men have equal rights in the workplace and in the domestic sphere to do the household chores and bearing the children. The social movement also proved effective in providing an understanding to public that ensuring exclusive breastfeeding is a responsibility for all stakeholders.